Prestige and loan pricing - Alexander Muermann; Thomas Rauter (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
We find that prestigious companies pay lower spreads and upfront fees on their loans despite the fact that prestige does not predict default risk over the life of the loan. Using survey data on firm-level prestige, we show that a one standard deviation increase in prestige reduces loan spreads by 6.18% per year and upfront fees by 22.86%. We identify causal effects (i) using fraud by industry peers as an instrument for borrower prestige and (ii) exploiting a regression discontinuity around rank 100 of the prestige survey. Banks that lend to prestigious firms attract more business afterwards compared to otherwise similar institutions. Moreover, the effect of prestige on upfront fees is particularly strong for new bank relationships. Our findings suggest that prestigious firms receive cheaper funding because the associated lending relationship helps banks establish valuable credentials they use to compete for future borrowers.
urn:nbn:de:hebis:30:3-416830
Keywords: G21; G30; G32; 330; Loan Pricing; Firm Prestige; Bank Incentives